(untitled) (Research, Society and Development, 2020)
The expressions of science and art go through categories ranging from music to literature, to the understanding of natural phenomena. There is nothing better than working on these issues in the youth and adult education (YAE) in a dimension of approximation of the meanings of the world that is subject to science. In this sense, the present work is a bibliographic research, with a qualitative focus where the interrelationship between science, art and literature will be the paths taken to guarantee the rights of YAE. As they are expressions of a civilization that has, in its social moments, singular ways of life, the article presents, from the junctions of the expressive forms of science and art, to search for necessary elements that are established between these two knowledge that unify paradigms within a world complexity that shows itself different, but unique, every moment. We sought to translate the aspects that bring together the two dimensions related to art and culture brought to the YAE clipping, to observe what constitutes and complement this knowledge in YAE. Therefore, questions were raised that pointed out some of the productions of the social subjects who played and play the constitutive ideas about the world, seeking in them the interaction between science and art, with literature focused on YAE.